Impact of the hole orientation of asymmetric GEM foils on the performance of single and triple GEM detectors. (27th October 2021) - Bouhali, O.; Hoepfner, K.; Ivone, F.; Kamon, T.; Keller, H.; Malhotra, S.; Al Rashdi, B.
Abstract: The Gas Electron Multiplier (GEM) foil is an amplification stage that has been introduced to overcome the problem of discharges observed in gaseous detectors. There are two major production techniques of GEM foils: double-mask and single-mask etching. Despite being an effective method, an asymmetry is observed between the top and bottom diameters of GEM holes in single mask technique compared to double mask one. In this paper we describe extensive simulations and measurements to study this hole asymmetry and its effect on the performance of GEM based detectors. The experimental data is collected using GEM foils of various hole geometries and orientations. In simulations, the same dimensions are used to study the properties of the detector. Simulations are performed with the Garfield ++ simulation package along with ANSYS for creating the geometry of the GEM foils as well as the triple-GEM detector and the meshing needed for the field calculations. The simulation results match the observations from experimental studies. The gains measured with single and triple-GEM detectors are lower if asymmetric foils are oriented with the smaller diameters towards the readout plane. Detailed simulation of the amplification and collection steps indicates that the lower gain is attributed to a loss of electrons at the GEM3 foil for the first time.